Deficiency of Sirtuin 1 Impedes Endometrial Decidualization in Recurrent Implantation Failure Patients - Li, Jiaxing; Qi, Jia; Yao, Guangxin; Zhu, Qinling; Li, Xinyu; Xu, Rui; Zhu, Zhenyi; Zhao, Hanting; Wang, Yuan; Ding, Ying; Sun, Yun (Frontiers in Cell and Developmental Biology, 2021)
Decidualization is driven by differentiation of human endometrial stromal cells (ESCs), and is a prerequisite for successful implantation and establishment of pregnancy. The critical role of impaired decidualization in women suffered recurrent implantation failure (RIF) has been established, while the underlying mechanism is poorly understood. In the present study, we verified the essential role of Sirtuin1 (SIRT1) in regulating differentiation and maintaining reactive oxygen species (ROS) homeostasis of human ESCs during decidualization. The abundance of SIRT1 was decreased in RIF patients both in the endometria during window of implantation phase and in the decidualized ESCs. Downregulation of SIRT1 disrupted the intracellular ROS homeostasis during decidualization of ESC, manifested as the accumulation of intracellular ROS level and the reduction of antioxidant stress molecules. Elimination of ROS with N-acetyl-L-cysteine (NAC) could rescued the decidualization inhibition caused by SIRT1 knockdown. Further, we explored the insufficient expression of SIRT1 in ESC affected the deacetylation of forkhead box O1 (FOXO1), and thus inhibited the transcriptional activity of FOXO1. This could account for the dysregulation of intracellular ROS homeostasis during decidualization and decreased expression of decidual markers. Collectively, our findings provided insight into the role of down-regulated SIRT1 in the poor decidual response of ESCs in RIF patients.